Pengenalan Bahasa Inggris dengan Metode Story Telling pada Anak Usia Dini di RA Bakti Telang Bangkalan Madura - Zulkhaeriyah, Zulkhaeriyah; Zakiyah, Fitriyatuz; Romadlan, M. Masqotul Imam; Awwaliah, Luthfi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
This activity aims to introduce young children to English by using storytelling in classroom learning. This activity was carried out at one of the kindergarten schools in Bangkalan, Madura, namely RA Bakti Telang. The target participants were students in group B. Theory and practical methods were combined in this activity to stimulate young children's curiosity in learning English. The results showed that the storytelling method could increase young children vocabularies. This is proven based on the results of the pre-test and post-test comparative evaluation. Storytelling could make young children understand new vocabularies in English easier.